(untitled) (Journal of the Bangladesh Agricultural University, 2026)
In Bangladesh, most farm households store paddy for consumption, emergencies, and seed’, but they rely on traditional methods that are vulnerable to insects, rodents, and mold. The study examined farmers’ perceptions of hermetic bags for paddy seed storage, their correlations with attributes, and the problems they faced in using hermetic bags. The research was conducted in the Phulpur upazila of Mymensingh district. From a population of 100 hermetic bag users, 80 paddy farmers were selected through simple random sampling following Slovin’s formula. Primary data were collected through face-to-face interviews using a structured interview schedule during January–February 2022. Farmers’ perception was measured using a 10-item, five-point Likert scale (1 = strongly disagree to 5 = strongly agree). Descriptive statistics and Karl Pearson’s Product Moment Correlation were employed for data analysis. Results indicated that 70% of the respondents exhibited a favorable perception toward hermetic bags as an effective method for storing paddy seeds. Significant positive correlations were observed between perception and age, education, farm size, training exposure, and extension media contact. Regarding problems, 83.33% of the farmers experienced a moderate level of problems in using hermetic bags, suggesting the presence of practical and knowledge-related limitations despite overall positive attitudes. Since most farmers showed a favorable perception of hermetic bags despite facing moderate problems, extension agencies should emphasize farmer training, technical support, and awareness programs to enhance effective adoption and reduce practical limitations in paddy seed storage. J Bangladesh Agril Univ 24(2): 177–186, 2026